Third-order nonlinear optical properties of the "clicked" closed-ring spiropyrans. (March 2019) - Zhao, Pengzhen; Wang, Dong; Gao, Hong; Zhang, Jingjing; Xing, Yan; Yang, Zhou; Cao, Hui; He, Wanli
Abstract: A series of the novel spiropyrans featuring nonplanar and spiro-conjugation structure have been successfully synthesized by [2 + 2] cycloaddition click reactions and characterized. UV-Vis absorption spectroscopy was used to analysis the photophysical properties and the click reactions. The initial absorption wavelength of the spectrum of the clicked products were extended to the near-infrared region in varying degrees. The electrochemical properties have been studied by the cyclic voltammetry (CV) measurement, and the band gaps ofSP, SP-E, SP-Q andSP-F 4 were narrowed in sequence. The third-order nonlinear optical(NLO) properties were investigated by the Z-scan technique at 532 nm, which indicated that all products had relatively good third-order NLO properties, and the product clicked by TCNQ performed the best third-order NLO properties. These results provide a new insight for the further research and design of the NLO materials. Graphical abstract: The closed-ring spiropyran dyes with complex conjugated π-electron structure modified by click reaction perform relatively good third-order NLO properties. Highlights: A series of novel spiropyrans with complex conjugated π-electron structure synthesized by a convenient and robust method. The closed-ring spiropyran dyes after the modification of [2 + 2] click reaction behaved relatively excellent NLO properties. The "clicked" closed-ring spiropyrans behaved special solvatochromic behaviour and relatively good solubility.